Recurrent lymphangioma: What are the treatment options? - Okoro Philemon; Anyaeze Chineme; Ngaikedi Charles (Wolters Kluwer Medknow Publications, 2009)
This is a report of a rerecurrence of extensive lymphangioma involving the neck, chest and both breasts of a female. The patient has had recurrence of the lesion twice following surgical excision. Surgery alone seemed to be insufficient in this case. Could adjunct of sclerotherapy have made a difference at the first surgery? Faced with a third recurrence, what other options are left? We report this case to highlight the difficulties and dilemma in managing extensive lymphangiomas.